2011
DOI: 10.1007/s00330-011-2293-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous removal of sentinel lymph nodes in a swine model using a breast lesion excision system and contrast-enhanced ultrasound

Abstract: Intradermal injection of microbubbles and CEUS can identify sentinel lymph nodes • Ultrasound could then guide percutaneous removal of intact and complete SLNs • We have shown this was feasible in pigs but not yet in humans • This technique may eventually have the potential to reduce futile SLN biopsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Sentinel LNs enhancement patterns were associated with the metastatic status of the nodes, but a direct clinical application is nonetheless limited as a result of the low sensitivity and specificity. No adverse event was reported following lymphosonography in client‐owned dogs with MCTs, which confirms the safety of this technique 27,29,31,32,44 …”
Section: Discussionsupporting
confidence: 65%
“…Sentinel LNs enhancement patterns were associated with the metastatic status of the nodes, but a direct clinical application is nonetheless limited as a result of the low sensitivity and specificity. No adverse event was reported following lymphosonography in client‐owned dogs with MCTs, which confirms the safety of this technique 27,29,31,32,44 …”
Section: Discussionsupporting
confidence: 65%
“…This result was repeated in a further 80-patient UK study [ 25 ]. In 2013, a larger study of 347 patients also found a low sensitivity of 61 % but a specificity of 100 % [ 26 ]. In the above three studies, there was no significant difference between the identification rates by CEUS and standard dual technique.…”
Section: Discussionmentioning
confidence: 99%
“…The constraints of the existing SLN biopsy techniques have led to the development of alternative methods. Indocyanine green fluorescence (ICG) [ 18 20 ], superparamagnetic iron oxide nanoparticles (SPIO) [ 21 , 22 ], and contrast-enhanced ultrasound (CEUS) using microbubbles have been reported as new feasible alternative techniques for the SLN biopsy in breast cancer [ 23 26 ]. Sulfur hexafluoride microbubbles is the most popular ultrasound contrast agent at present, which plays a role as an inert gas in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Sever et al . ( 31 ) injected SonoVue ® that was mixed with blue dye around the mammary papillae in two young pigs. The enhancing superficial inguinal lymph nodes were easily identified and successfully removed percutaneously by the breast lesion excision system (BLES).…”
Section: Review Of Literaturementioning
confidence: 99%